Manajemen Perguruan Tinggi Keagamaan Islam Di Era Revolusi Industri - almuarif, almuarif; Iqbal, Muhamad; Hadi, Akmal; Iswantir (STAIN Bengkalis, 2023)
In an effort to reconstruct and reposition Islamic Religious Higher Education (PTKI) in this modern era, it is important to change our perspective and increase awareness of the true role of Islamic education. This is not only related to the ability of each PTKI to compete with leading universities in the world, but also about a greater responsibility, namely fighting for Islamic values in the context of national life. Apart from producing intellectually competent graduates, PTKI is also responsible for forming noble characters. This research uses the